PENGARUH PERENCANAAN PAJAK, LEVERAGE DAN PROPORSI DEWAN KOMISARIS INDEPENDEN TERHADAP MANAJEMEN LABA - Khotimah, Khusnul; Pahala, Indra; Nasution, Hafifah (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
The purpose of this study is to determine the effect of tax planning, leverage and the proportion of independent board of commissioners on earnings management of consumer non-cyclicals companies on the IDX for the period 2020-2022. The type of this study is quantitative, and the data used are secondary data. The sample used in this study were 80 companies with a total of 240 observational data obtained using purposive sampling techniques. The analytical method used is panel data regression analysis and using Eviews 12 software. Based on the results of this study, it shown that (1) tax planning has no effect on earnings management, (2) leverage does not affect earnings management and (3) the proportion of independent board of commissioners has a negative effect on earnings management